Table of Contents

**Definition**: inverse mapping

t = (z-z1)/(z2-z1)

theta = (1-t)*theta1 + t*theta2

x’=x*cos(theta)+y*sin(theta)

y’=-x*sin(theta)+y*cos(theta)

**Call**: hfTwistZ(xt,z1,z2,theta1,theta2);

**Parameters**:

xt - point coordinates array to be changed

z1, z2 - end points of z-interval

theta1, theta2 - rotation angles in radians for end points

**Test file**: twist.hf

**Definition**: inverse mapping

t = (y-y1)/(y2-y1)

theta = (1-t)*theta1 + t*theta2

z’=z*cos(theta)+x*sin(theta)

x’=-z*sin(theta)+x*cos(theta)

**Call**: hfTwistY(xt,z1,z2,theta1,theta2);

**Parameters**:

xt - point coordinates array to be changed

z1, z2 - end points of z-interval

theta1, theta2 - rotation angles in radians for end points

**Test file**: twist.hf

**Definition**: inverse mapping

t = (x-x1)/(x2-x1)

theta = (1-t)*theta1 + t*theta2

y’=y*cos(theta)+z*sin(theta)

z’=-y*sin(theta)+z*cos(theta)

**Call**: hfTwistX(xt,z1,z2,theta1,theta2);

**Parameters**:

xt - point coordinates array to be changed

z1, z2 - end points of z-interval

theta1, theta2 - rotation angles in radians for end points

**Test file**: twist.hf